2010
DOI: 10.1007/s11999-010-1381-x
|View full text |Cite
|
Sign up to set email alerts
|

Should We Be Teaching Information Management Instead of Evidence-based Medicine?

Abstract: To encourage high-quality patient care guided by the best evidence, many medical schools and residencies are teaching techniques for critically evaluating the medical literature. While a large step forward in many regards, these skills of evidence-based medicine are necessary but not sufficient for the practice of contemporary medicine and surgery. Incorporating the best evidence into the real world of busy clinical practice requires the applied science of information management. Clinicians must learn the tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
1
13
0
1
Order By: Relevance
“…Trusted, high-quality information-gathering services should be used instead of attempting to read original research literature : The skills needed for the classic EBM approach of acquiring original research, assessing it for validity and applying the results are less relevant now that there are robust literature survey services that do this work and provide short, accessible summaries 13 28. A participant explains:…”
Section: Resultsmentioning
confidence: 99%
“…Trusted, high-quality information-gathering services should be used instead of attempting to read original research literature : The skills needed for the classic EBM approach of acquiring original research, assessing it for validity and applying the results are less relevant now that there are robust literature survey services that do this work and provide short, accessible summaries 13 28. A participant explains:…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, others recommend instead greater emphasis on teaching skills for information management over teaching traditional EBM skills [ 33 , 34 ]. The rationale is that skill to quickly identify sources of relevant, synthesized, and contextualized information is highly advantageous in time constrained environments and more conducive to rapid end-user uptake of the best available research [ 5 , 33 , 34 ]. Importantly, however, the caveat is that robust and applicable syntheses are also readily accessible [ 5 , 11 , 34 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has revealed the role of clinical evidence to be limited through other factors in clinical practice. These factors included lack of resources, lack of time, inadequate skills and inadequate access to find, evaluate and use published clinical evidence at the point of care [28–30]. Other limiting factors comprised individual patient complexity, personal practice, clinical experience, opinions of colleagues, pathophysiologic rationale, goals and values of patients and other stakeholders, health care system features and a general reservation towards published clinical evidence, due to the influence of experts and editors along the publication process [4–7].…”
Section: Discussionmentioning
confidence: 99%